Literature Review Analisis Peran Pasar Uang dalam Sistem Keuangan - Arin Zahra; Chika Kamelia; Madinatul Munawaroh (Kajian Ekonomi dan Akuntansi Terapan, 2026)
The money market plays a vital role in the global financial architecture as a provider of short-term liquidity and a primary channel for monetary policy transmission. This research is motivated by the rapid transformation of financial instruments, which now encompass conventional and Sharia-compliant sectors, as well as digital innovations such as e-money and stablecoins. The purpose of this study is to examine the concept of the money market, identify the diversity of modern instruments, and analyze their strategic role in economic stability through a qualitative literature review approach. The analysis shows that the money market is highly effective in managing bank cash reserves and controlling inflation by regulating the money supply. The presence of digital instruments has been proven to accelerate liquidity flows, while Sharia schemes provide transparent and equitable investment alternatives. However, the emergence of digital assets also brings challenges of volatility that require adaptive regulation and professional skepticism from market participants. The implications of this research emphasize the importance of synergy between monetary authorities and financial technology to address global disruption. Strengthening regulations on future instruments is expected to create a more inclusive and stable financial system that can respond precisely to economic shocks.